Computational fluid dynamics as a tool for improving stroke technique - Cohen, R. C. Z.; Clearly, P. W.; Harrison, S. M.; Mason, B. R.; Pease, D. L. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Human swimming is a highly competitive sport where performance has a complex dependence on technique, fluid dynamics, biomechanics, and physiology. Computational fluid dynamics (CFD) is increasingly being used as a tool to study elite level human swimming. This approach complements traditional pool based experimentation, providing previously unobtainable data to provide new insights into the relationships between stroke technique and performance. In this paper, pool based experimentation is reviewed along with recent developments in the field of swimming CFD. Finally, the future directions of the field of swimming CFD are proposed which will see it become an indispensible tool for elite athletes seeking improved stroke technique.